Raízes de números complexos: uma sequência didática - Costa Júnior, Cleber Luis Alves (2019)
This dissertation aims to present a didactic sequence with a mathematical research approach, where the teacher will have several activities at a gradual level of deepening to show a geometric relationship between the nth roots of a complex number and the vertices of a regular polygon. In order to make this investigation more palatable for students’ comprehension, a programming has been developed in the MATLAB software, where students manipulate or use the application to calculate the roots and responses of the dynamically and efficiently generated picture.